2015
DOI: 10.1016/j.ijsu.2014.11.052
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic appendicectomy in obese is associated with improvements in clinical outcome: Systematic review

Abstract: Laparoscopic appendicectomy appears to be a safer alternative approach to open surgery in obese adult patents. There is no significant difference in the outcomes between the obese and non-obese patients undergoing laparoscopic appendicectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 19 publications
0
22
1
Order By: Relevance
“…A meta-analysis of prospective and retrospective comparative series evidences superiority of LA vs. OA also in obese (BMI >30) patients [ 92 ]. Dasari et al reported the same encouraging results also in a recent Systematic Review [ 93 ].…”
Section: Resultsmentioning
confidence: 55%
“…A meta-analysis of prospective and retrospective comparative series evidences superiority of LA vs. OA also in obese (BMI >30) patients [ 92 ]. Dasari et al reported the same encouraging results also in a recent Systematic Review [ 93 ].…”
Section: Resultsmentioning
confidence: 55%
“…This was confirmed by a meta-analysis, although a reduced length of hospital stay was noted after LA [105]. More recently, two recent meta-analyses showed a reduction of mortality and morbidity rates after LA [106, 107]. …”
Section: Pre-operative Carementioning
confidence: 79%
“…LA also appears to be a safer alternative approach to OA in obese adult patients. In the systematic review by Dasari et al including seven retrospective cohort studies and one randomized controlled trial, LA in obese patients was associated with reduced mortality (RR 0.19), reduced overall morbidity (RR 0.49), reduced superficial SSI (RR 0.27), and shorter operating times and postoperative length of hospital stay, compared to OA [156].…”
Section: Q44: Does Laparoscopic Single-incision Surgery Confer Any mentioning
confidence: 99%